Different mechanisms of protein immobilization on glutaraldehyde activated supports: Effect of support activation and immobilization conditions - Betancor, Lorena; López-Gallego, Fernando; Hidalgo, Aurelio; Alonso-Morales, Noelia; Mateo, Gisela Dellamora-Ortiz Cesar; Fernández-Lafuente, Roberto; Guisán, Jose M. (Enzyme and microbial technology, 2006)
The precise control of the conditions during support activation with glutaraldehyde has enabled the modification of the amino groups of the matrix with one or two glutaraldehyde molecules. Moreover, the use of aminated supports implies that below each glutaraldehyde molecule, there are amino groups and, therefore, these supports could be considered as heterofunctional matrices; an anion exchanger bearing glutaraldehyde groups for covalent immobilization. Thus, by using several enzymes as models, it has been found that at low ionic strength the protein immobilization on glutaraldehyde activated supports proceeds via a first ionic interchange of the protein on the amino groups of the support, followed by the covalent reaction. Moreover, the dimeric form of glutaraldehyde seems to be much more reactive than its monomeric counterpart, permitting the immobilization of proteins even at very high ionic strength. Although in all cases the immobilization of the enzymes on both monomer and dimeric matrices promoted a significant increment in the enzyme stability, it was found that the stabilization depends on the degree of activation (monomer or dimer), and it is necessary to analyze each individual enzyme before selecting any of the immobilization protocols.